How the Educator 5.0 Will Not Be Replaced by AI: An Adaptive Microlearning Architecture Based on Augmented Intelligence - Ferreira, Emanuel; Quincozes, Silvio E.; Ciocca, Matheus M.; Silva, Gabriel; Souza, Paulo; Guedes, Gilleanes; Silva, Williamson (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
Education 5.0 proposes a human-centered model that integrates personalization, technology, and the active roles of both instructors and students. However, current educational tools still face limitations such as a lack of flexibility and monitoring capabilities. This work proposes an educational architecture that supports the Educator 5.0 in generating, customizing, and monitoring adaptive microlearning paths. The concept of augmented intelligence enhances the educator’s role as a critical curator of AI-generated content, based on their teaching materials, and as a mediator of formative learning experiences. As a result, learners obtain customized, real-time adaptive content blocks, ensuring learner diversity is respected and enabling the generation of pedagogical alerts.